Findings vs. Interpretation in “The Long-Term Impacts of Teachers” by Chetty et al. - Adler, Moshe (Education Policy Analysis Archives, 2013)
The authors of the study “The Long-Term Impact of Teachers” claim that their study shows that increases in teacher value-added lead to significant and lasting increases in test scores and significant increases in income that will last throughout adulthood. Instead, I show that these claims are false because they are contradicted by the findings of the study itself. In fact, the results of the Chetty et al. study raise serious questions about the benefits of using the value-added method for evaluating teachers.